2021
DOI: 10.1101/2021.11.10.467254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reliability of quantitative multiparameter maps is high for MT and PD but attenuated for R1 and R2* in healthy young adults

Abstract: We investigate the reliability of individual differences of four quantities measured by magnetic resonance imaging based multiparameter mapping (MPM): magnetization transfer (MT), proton density (PD), longitudinal relaxation rate (R1), and effective transverse relaxation rate (R2*). A total of four MPM datasets, two on each of two consecutive days, were acquired in healthy young adults. On Day 1, no repositioning occurred; on Day 2, participants were repositioned between MPM datasets. Using intra-class correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 61 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Presence of diamagnetic elements causes R2* to overestimate iron content and QSM to underestimate it ( Haacke et al, 2005 ). Although both QSM and R2* were available, for the present study we favoured QSM over R2*, as Wenger et al (2021) recently showed poor reliability of R2* in regions outside basal ganglia (see section “MRI Acquisition and Preprocessing” Methods for further detail).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Presence of diamagnetic elements causes R2* to overestimate iron content and QSM to underestimate it ( Haacke et al, 2005 ). Although both QSM and R2* were available, for the present study we favoured QSM over R2*, as Wenger et al (2021) recently showed poor reliability of R2* in regions outside basal ganglia (see section “MRI Acquisition and Preprocessing” Methods for further detail).…”
Section: Discussionmentioning
confidence: 97%
“…Relaxometry was also available in the study (see Salami et al, 2021 ). However, R2* has been observed to have poor reliability in regions outside the basal ganglia ( Wenger et al, 2021 ). For comparative purpose, post hoc analyses showed a good intraclass correlation (ICC; Koo and Li, 2016 for interpretation of ICC) of 0.798 for QSM in DLPFC, which was greater than R2* (0.730).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, impactful events that occur in between scans such as learning new skills (e.g. Wenger et al, 2021), or adverse events such as brain injury (e.g. Lindberg et al, 2019), will lead to lasting differences.…”
Section: Reliability and Stabilitymentioning
confidence: 99%
“…To address our first question (what is the longitudinal stability of grey matter measures in the ABCD study, and do they differ across brain regions, structural metrics, and testing sites?) we ran a series of ICED models (Brandmaier, Wenger, et al, 2018; for other applied studies, see Anand et al, 2022;Wenger et al, 2021). We estimated between-subject and error variances for three grey matter measures (cortical thickness, surface area, and volume) across regions of interest.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation